Analisis Konstanta Euler-Mascheroni yang Diperumum pada Deret Harmonik - Rahman, Raisha Inayah; Rahman, Hairur; Herawati, Erna (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
The generalized Euler-Mascheroni constant analyzes functions or sequences with specific parameters in various scientific fields. As scientific knowledge advances, the generalized Euler-Mascheroni constant continues to undergo renewal. One example is found in